Fission yeast Ish1 and Les1 interact with each other in the lumen of the nuclear envelope. (13th September 2022) - Asakawa, Haruhiko; Hirano, Yasuhiro; Shindo, Tomoko; Haraguchi, Tokuko; Hiraoka, Yasushi
Abstract: The nuclear envelope (NE) provides a permeable barrier that separates the eukaryotic genome from the cytoplasm. NE is a double membrane composed of inner and outer nuclear membranes. Ish1 is a stress‐responsive NE protein in the fission yeast, Schizosaccharomyces pombe . Les1 is another NE protein that shares several similar domains with Ish1, but the relationship between them remains unknown. In this study, using fluorescence and electron microscopy, we found that most regions of these proteins were localized within the NE lumen. We also found that Ish1 interacted with Les1 via its C‐terminal region in the NE lumen and that the NE localization of Ish1 depended on the C‐terminal region of Les1. Ish1 and Les1 were co‐localized at the NE in interphase cells, but when the nucleus divided at the end of mitosis (closed mitosis), they showed distinguishable localization at the midzone membrane domain. These results suggest the regulated interaction between Ish1 and Les1 in the NE lumen, although this interaction does not appear to be essential for cell survival. Abstract : The nuclear envelope provides a permeable barrier that separates the eukaryotic genome from the cytoplasm. In this study, using fluorescence and electron microscopy, we found that most regions of Ish1 and Les1 are localized within the NE lumen, and that Ish1 interacts with Les1 via its C‐terminal region in the NE lumen.